Programas de residência multiprofissional em saúde da família: potencialidades e desafios dos cursos no Brasil - Silva, Gilson Fernandes da (2024)
The Multiprofessional Residency Programs in Family Health (PRMSF), a form of teaching-service integration, aim to train health professionals to work in the Family Health Strategy (ESF), in line with the National Policy for Continuing Education in Health (PNEPS). This research aimed to problematize and analyze the challenges and potentialities of PRMSF in training professionals for the Unified Health System. This is an exploratory, descriptive study with a quantitative and qualitative approach, developed on a national scale. Coordinators of PRMSF programs implemented until 2018 participated. Data were collected via an online questionnaire available on Google Forms from October 2022 to March 2023. Quantitative data were systematized and distributed according to absolute and relative frequencies, and qualitative data were subjected to thematic analysis, which are presented in six articles. The first article, mapping PRMSF implemented in Brazil in terms of management, organization, and financing, revealed that PRMSF are concentrated in the South region, are mostly funded by the Ministry of Health, with nursing being the most common profession, and primary care as the most common area of concentration. The second article describes the didactic-pedagogical strategies for training in family health and points out that PRMSF need to reinforce didactic-pedagogical strategies that strengthen a multiprofessional, interdisciplinary, critical-reflective stance and enable educational experiences guided by the SUS and PNEPS guidelines. The third article describes the processes of planning and implementing training in PRMSF and points to the creation of training policies aimed at the qualification and valorization of professionals, whether at the federal, state, or municipal levels, with a view to ensuring a professional profile grounded in multiprofessional, interdisciplinary, and interinstitutional characteristics. The fourth article describes how the articulation between the management spheres of PRMSF occurs, revealing the need to adopt participatory and collegial co-management instruments by professionals from different areas of action, in addition to co management by the three administrative spheres. The fifth article identifies the actions developed in a multiprofessional manner by PRMSF professionals and residents and argues that a collective effort from all administrative spheres is necessary to adopt measures to mitigate and/or resolve the weaknesses that have been hindering the effective development of professional competencies and formative processes carried out by PRMSF. The sixth article identifies the articulation of PRMSF initiatives with continuing education in health and describes how PRMSF coordinators evaluate the relationship between training and the performance of professionals in the SUS. PRMSF favor the integration between residents, the health team, and the community, reorganizing the work process in the scenarios in which they are inserted and thus presenting improvements in the quality of care provided to users. It is concluded that the programs are a promising strategy for qualifying primary care, although they could be expanded in number, pedagogical approaches, actions to valorize the actors involved, inter-federative co-management strategies, professional competencies during training, and recognition of PRMSF as a strategy to strengthen Continuing Education in Health within the scope of Primary Care.